Educating for Global Citizenship: Conflicting Agendas and Understandings - Shultz, Lynette (Alberta Journal of Educational Research, 2007)
Educating for global citizenship is increasingly named as a goal of education. This study examines the variations in intent and approach to global education and educating for global citizenship. A review of the literature identifies the links between citizenship and globalization as well as the conflicting discourses and agendas surrounding citizenship education in a globalized neoliberal policy context. Using a conceptual framework that highlights three contrasting approaches to globalization—a neoliberal approach, a radical approach, and a transformational approach—this article compares three global education policies and their citizenship education approaches and highlights the issues implicit in each as well as the problems and possibilities for furthering a social justice agenda. The article concludes that education for global citizenship is a complex and contested concept and that educators who claim to be educating for global citizenship must be clear on the implications of their work.